Inhibitors from Natural Products to HIV-1 Reverse Transcriptase, Protease and Integrase - Jiang, Y.; B. Ng, T.; R. Wang, C.; Zhang, D.; H. Cheng, Z.; K. Liu, Z.; T. Qiao, W.; Q. Geng, Y.; Li, N.; Liu, F. (Mini Reviews in Medicinal Chemistry, 2010)
Acquired immunodeficiency syndrome (AIDS), caused by human immunodeficiency virus type 1 (HIV-1) infection, is still one of the most challenging diseases of the early 21st century. Reverse transcriptase (RT), protease (PR) and integrase (IN) are three key enzymes of HIV-1. Despite the shortcomings of chemical drugs such as toxicity, lack of curative and multiple effects, the search for more and better anti-HIV agents has been focused on natural products. Many natural products have been shown to possess promising activities that could assist in the prevention and amelioration of the disease. Most of these natural anti-HIV agents have other medicinal values as well, which afford them further prospective as novel lead compounds for the development of new drugs. These natural products can deal with both the virus and the various disorders that are caused by HIV. In this review, natural inhibitors of RT, PR and IN have been found to be classified and the relationship between structure and inhibitory activity is discussed.
Keywords: corilagin